Facile preparation of carbon nanotubes/cellulose nanofibrils/manganese dioxide nanowires electrode for improved solid-sate supercapacitor performances - Siew, Xian Chin; Kam, Sheng Lau; Ginting, Riski Titian; Sin, Tee Tan; Poi, Sim Khiewcc; Chin, Hua Chia; Wongchoosuk, Chatchawal (Multidisciplinary Digital Publishing Institute, 2023)
Wearable energy storage devices require high mechanical stability and high-capacitance flexible electrodes. In this study, we design a flexible supercapacitor electrode consisting of 1-dimensional carbon nanotubes (CNT), cellulose nanofibrils (CNF), and manganese dioxide nanowires (MnO2 NWs). The flexible and conductive CNT/CNF-MnO2 NWs suspension was first prepared via ultrasonic dispersion approach, followed by vacuum filtration and hot press to form the composite paper electrode. The morphological studies show entanglement between CNT and CNF, which supports the mechanical properties of the composite. The CNT/CNF-MnO2 NWs electrode exhibits lower resistance when subjected to various bending angles (−120–+120°) compared to the CNT/CNF electrode. In addition, the solid-state supercapacitor also shows a high energy density of 38 μWh cm−2 and capacitance retention of 83.2% after 5000 cycles.